Cloning, expression and characterization of a HER2-alpha luffin fusion protein in Escherichia coli. Issue 8 (14th September 2019) - Barkhordari, Farzaneh; Sohrabi, Nooshin; Davami, Fatemeh; Mahboudi, Fereidoun; Garoosi, Yeganeh Talebkhan
Abstract: In recent decades, immunotoxins have attracted significant attention in treatment of a wide range of diseases including cancers due to their natural origins and their role in blocking crucial pathways within the cells. Ribosome inactivating proteins (RIPs) are efficient molecules in blocking protein synthesis through interactions with ribosomal rRNA molecules. cDNA molecule encoding HER2 scFv antibody fragment originated from trastuzumab attached to the mature alpha luffin gene fragment was subcloned into pET28a expression vector and expressed in different E. coli expression hosts. Identity of the expressed recombinant protein was investigated through western blotting and the fusion protein was purified using Ni-NTA affinity chromatography. The biological activity (toxicity) of the protein was investigated on DNA and RNA samples. A 58 kDa protein was expressed in E. coli . The best protein expression level was achieved in 0.2 mM IPTG at 30 °C in TB medium using E. coli BL21 (DE3) host strain. The fusion protein showed RNase and DNA glycosylase activity on tested RNA and DNA samples. DNA glycosylase activity of the recombinant fusion protein showed that alpha luffin part of this protein is active in conjugation to the scFv molecule and the expressed protein can be further studied in targeted biological in vitro assays.